Radical rearrangement of aryl/alkylidene malononitriles via aza michael addition/decynoformylation/addition sequence: an access to alpha-aminonitriles and alpha-aminoamides - Bhoite, Shubhangi P.; Bansodes, Ajay H.; Suryavanshi, Gurunath (Journal of Organic Chemistry, 2020)
An efficient, safe, and environmentally friendly tertiary butyl hydrogen peroxide (TBHP)-mediated rearrangement of aryl/alkylidene malononitrile with anilines has been developed with in situ generation of HCN as the cyanide source for the synthesis of substituted alpha-aminonitriles and alpha-aminoamide. A diverse set of alpha-aminonitriles and alpha-aminoamides was efficiently synthesized in good to excellent yields. This method features a broad substrate scope and good functional group tolerance, and the in situ-generated HCN bypasses the use of an external cyanide source.